¿Regulación sectorial o normas de competencia?: El principio de supletoriedad en el caso Speedy Naked - Lercari Bueno, Alessia (2021)
This paper analyses the supplementary application of competition laws in Peru, and it assesses the criteria established in the procedure initiated against Telefónica del Perú S.A.A. for the alleged abuse of its dominant position in the form of tying. It outlines the scope for the supplementary application of competition laws and provides a definition that intends to preserve the integrity of the legal system when conflicts between regulation and competition arise.